A multilayer coarse-grained molecular dynamics model for mechanical analysis of mesoscale graphene structures. (30th June 2021) - Liu, Sihan; Duan, Ke; Li, Li; Wang, Xuelin; Hu, Yujin
Abstract: Graphene-based structures have found widespread applications in the fabrication of superior composite materials, conductors, and sensors owing to their excellent properties. Molecular dynamics (MD) simulation is often used to gain an in-depth understanding of the mechanical behaviors of those structures. However, MD simulation of mesoscale graphene structures faces great challenges due to its limited model size or high computation cost. In this work, we proposed a multilayer coarse-grained (CG) MD model which coarsens graphene layers in both planar and thickness directions. We systematically investigated the effect of coarse-graining on simulation accuracy in the CG-MD model. The optimal coarse-graining parameters for simulating the mechanical behaviors of graphene in tension, shearing, adhesion, bending, and self-folding were obtained. Our optimal CG-MD model enabled the simulation of relatively large-scale graphene structure with 1 ∼ 2 orders of magnitude increase in length and 3 ∼ 4 orders of magnitude reduction in computational time compared with the all-atom (AA) model, offering a valuable tool for designing and exploring graphene-based novel materials. Graphical abstract: Image 1 Highlights: A new CG model has been developed, which can coarsen a multilayer graphene structure in both planar and thickness directions. The effect of coarse-graining on the simulation accuracy/efficiency has been systematically investigated for the first time. The improved CG model produces considerably high computation efficiency, over 5000 times faster than the AA model. Our CG model enables the simulation of a number of mesoscale graphene-based structures that can't be done by the AA model.